THE CONDITION OF RECEIVABLES TURNOVER AND FIRM SIZE ON PROFITABILITY (ROA) - Anggadini, Sri Dewi (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2018)
Profitability (ROA) is the company's ability to earn a profit or advantage. The purpose of this research was to test and analyze the effect of the rotation and the size of the company's receivables against the profitability (ROA). The research method used is descriptive method quantitative approach with verifikatif. This research uses a 13 company as its population and 10 companies that serve as samples on the automotive sector sub manufacturing companies listed on the Indonesia stock exchange period 2011-2015, with purposive sampling technique While using the methods of analysis used in this study was multiple linear regression on the significance level of 5%. The program used in analyzing data using Statistical for Social Sciences (SPSS) ver. 16.0. Research is shows that partially turnaround receivable and the size of the company has influence significantly to profitability (ROA). With the huge influence of each are medium and low. Keyword: Receivable turnover, Firm size, Profitability (ROA)